2009
DOI: 10.1007/s10745-009-9284-8
|View full text |Cite
|
Sign up to set email alerts
|

Viewing Change Through the Prism of Indigenous Human Ecology: Findings from the Afghan and Tajik Pamirs

Abstract: The effects of socioecological transformations such as climate change, the collapse of the Soviet empire, and civil war are examined for 14 villages in the valleys of the Pamir Mountains in the historical Badakhshan region, now divided between Afghanistan and Tajikistan. Preliminary findings indicate concern for food sovereignty, evidence of biocultural impacts of climate change, an increasing burden on women, debilitating opium addiction, the ecological importance of sacred sites, and other priorities related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 13 publications
2
67
0
Order By: Relevance
“…This review indicated that climate change was primarily discussed in reference to water and soil quality, long-term ecosystem processes such as land degradation and grassland management and the availability of water for agriculture in the transboundary context. There was one publication by Kassam (2009) in which the author discussed the impacts of climate change on local culture, women, and sustainable livelihoods using the example of Tajikistan.…”
Section: Resultsmentioning
confidence: 99%
“…This review indicated that climate change was primarily discussed in reference to water and soil quality, long-term ecosystem processes such as land degradation and grassland management and the availability of water for agriculture in the transboundary context. There was one publication by Kassam (2009) in which the author discussed the impacts of climate change on local culture, women, and sustainable livelihoods using the example of Tajikistan.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the population of the Pamir directly depends on the natural environment and a lot of traditional knowledge exists (Kassam, 2009), lake outburst hazards are often neglected: the source area is usually far away from the area of impact and events occur at very long time intervals or as singularities. The Dasht 2002 GLOF hit the village completely unexpected -there was no awareness of the hazard and no preparedness for the event (Schneider et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The permanent settlements are concentrated close to the valley bottom and depend on irrigation with melt water. Transhumance to distant summer pastures in the upper valleys is common (Kassam, 2009). The climate is semi-arid to arid, with an annual mean precipitation of 288 mm.…”
Section: Study Areamentioning
confidence: 99%
“…Cold Tab. 4 Ten most frequently reported health problems and species with highest citation frequency for their treatment. or gently warmed infusions were applied as washes and baths for the treatment of scabies and other skin disorders.…”
Section: Mode Of Preparation Administration and Plant Parts Usedmentioning
confidence: 99%